Intimate Partner Violence in Same-Sex Relationships: Are We Aware of the Implications?. Issue 1 (January 2023) - Kar, Anindya; Das, Nabagata; Broadway-Horner, Matt; Kumar, Praveen
Intimate partner violence (IPV) has been a significant public health problem in same-sex relationships. However, health policies across the globe do not address IPV causing a massive gap in health and economic burden. In the last decade, crucial missing links have been established, and researchers tried to connect the dots of this severe health disparity. This intersectionality has found the impact of race, gender, class, physical ability, and legal framework of IPV in lesbian, gay, and bisexual (LGB) relationships. However, preventive strategies, training programs, and dialogues in the clinical field about IPV are from heteronormative lenses. This particular bias can perpetuate the issue and will remain one of the leading causes of health burden in the LGB population. This article reviews the lacunae in health policies regarding same-sex IPV, highlights its impact on minority mental health, and calls for attention to train health-care professionals regarding the same.